A search for trypanosoma brucei rhodesiense diagnostic antigens by proteomic screening and targeted cloning - Manful Gwira, Theresa; Mulindwa, Julius; Frank, Fernanda M.; Clayton, Christine; Matovu, Enock (PLOS ONE, 2010)
The only available diagnostic method for East African trypanosomiasis is light microscopy of blood samples. A simple immunodiagnostic would greatly aid trypanosomiasis control.
Gesehen am 03.05.2023